Constitutional reform and effective government - Sundquist, James L. (Washington, D.C. : Brookings Institution, 1986)
In this revised edition of his highly acclaimed 1986 volume, James Sundquist reviews the origins and rationale of the constitutional structure and the current debate about whether reform is needed, then raises practical questions about what changes might work best if a consensus should emerge that the national government is too prone to stalemate to meet its responsibilities.
Spine title: Constitutional reform.
Includes bibliographical references and index.
aia 22/11/2017
Loans
Keywords: Presidents; Separation of powers; Constitutional history; United States